Matricellular proteins tune myeloid‐derived suppressor cell recruitment and function in breast cancer. Issue 2 (1st February 2017) - Chiodoni, Claudia; Sangaletti, Sabina; Colombo, Mario P.
Abstract : Review on matricellular protein regulation of myeloid‐derived suppressor cell biology, and the consequent impact on breast cancer progression and metastasis. Abstract : Solid tumor progression is often associated with the expansion of myeloid‐derived suppressor cells (MDSCs), a heterogeneous population of immature myeloid cells that actively foster tumor growth and metastatic dissemination through a plethora of mechanisms, including, but not limited to, their major suppressive activity on the immune response. Indeed, MDSCs may sustain tumor progression by dynamically remodeling the tumor microenvironment through the production of angiogenic factors and metalloproteases, by helping the establishment of a premetastatic niche, and by promoting stemness and epithelial‐to‐mesenchymal transition (EMT) features in tumor cells. MDSCs are also regulated by a growing list of factors that mainly comprise 2 sets of signals: those responsible for their expansion and recruitment, such as GM‐, M‐, and G‐CSF and other growth factors, and those relevant for the induction of their suppressive activity, which include proinflammatory cytokines and transcription factors. We review here a new class of MDSC regulators—matricellular proteins—with a particular focus on osteopontin (OPN) and secreted acidic cysteine‐rich glycoprotein (SPARC), which seem to affect the expansion/recruitment and the immune‐suppressive activity of MDSCs. Matricellular proteins function indirectly on MDSCs through the induction of other mediators when produced by tumor cells and cell autonomously when expressed—likely in an intracellular form—directly by MDSCs.